The Effects of Destemming/Crushing and Pressing Conditions in Rosé Wine Production - Lorenzo Guerrini; Ferdinando Corti; Giulia Angeloni; Piernicola Masella; Agnese Spadi; Luca Calamai; Alessandro Parenti (Australian Journal of Grape and Wine Research)
Background and Aims. Rosé wines are becoming more popular, as is the demand for organic wines. However, there are few studies on the effects of operative choices on the quality and style of these wines. The paper aims to investigate the effects of the early stages of processing (destemming/crushing and pressing) on rosé wine characteristics. Methods and Results. A full factorial experiment was carried out on Sangiovese, considering two factors related to grape processing: the prepressing treatment (intact clusters or destemmed/crushed berries) and the pressing pressure. Sugars, ethanol, acidity, phenols, and color were measured in juices, while volatile compounds and sensory profiles were evaluated in wines. Destemming/crushing dramatically changed the composition of both juices and wines’; notably, acidity increased and floral and color intensities decreased in intact cluster samples. Furthermore, a clear interaction was found between prepressing treatment and pressure. Pressure, in turn, affected several acidity and color parameters. This could be related to the chemical composition and consistency of the different berry zone, which interact with the mechanical action of the destemmer/crusher and press. Conclusions. Processing choices affect all of the main qualitative features of rosé wine; they could be successfully used to decide the wine’s style and minimize the use of additives and adjuvants. Significance of the study: in rosé production, the capability to modulate the operational protocols allows selecting of different wines from the same grape batch. This represents a useful tool to optimize grape processing according to the company’s commercial priorities.